2022
DOI: 10.1111/csp2.12730
|View full text |Cite
|
Sign up to set email alerts
|

From boutique to mainstream: Upscaling wildlife‐friendly farming through consumer premiums

Abstract: Wildlife‐friendly produce shows promise in addressing the disconnect between consumers' choices and the loss of biodiversity from agriculture. However, the scope of programs and their contribution to conservation remain limited. An improved understanding of specific markets, combined with auspicious scenarios, could address this. In Australia's Murray‐Darling Basin, rice fields support the largest known breeding population of the Australasian bittern, a globally endangered waterbird. We surveyed 1478 Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…To help in the proliferation of BFF products and enhance biodiversity conservation across wider regions where local social capital does not work, it will be necessary to not only nurture interest in conservation but also to foster the types of consumer motivations observed in organic agriculture. For example, combining attributes, such as the use of conservation target species and eco‐friendly practices (e.g., reduction of synthetic pesticides/fertilizers), should be an effective promotion measure to motivate consumers to purchase BFF products (Herring et al, 2022; Mameno et al, 2023; Nishimura et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To help in the proliferation of BFF products and enhance biodiversity conservation across wider regions where local social capital does not work, it will be necessary to not only nurture interest in conservation but also to foster the types of consumer motivations observed in organic agriculture. For example, combining attributes, such as the use of conservation target species and eco‐friendly practices (e.g., reduction of synthetic pesticides/fertilizers), should be an effective promotion measure to motivate consumers to purchase BFF products (Herring et al, 2022; Mameno et al, 2023; Nishimura et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…This was significantly higher than the corresponding value of 24.3% of the population in 2022 statistics (https://www.stat.go.jp/data/jinsui/2022np/index.html, p < .001, prop‐test). Referring to items asked in questionnaire surveys of previous studies on BFF products (Herring et al, 2022; Sehra & MacMillan, 2021), the following socio‐demographic and general information was collected: sex, age, hometown, marital status, education, current occupation, annual income, number and school age of children, number of household members, and rice consumption rate was calculated by dividing the number of rice meals by the total number of meals in a week. To detect the degree of respondent's contact with agricultural environment, we asked whether there were paddy fields or other farmlands within a 1–2 min walk of their current residence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioural domains targeted at reducing biodiversity loss include those focused on lifestyle, stewardship, social, consumption, advocacy, and donation behaviors (Selinske et al., 2020). Within the domain of consumption behaviors, certification schemes have been shown to be effective in influencing consumption choices, and research into labeling schemes has demonstrated that many consumers are willing to accept a price premium in return for purchasing wildlife‐friendly products (Herring et al., 2022; Selinske et al., 2020).…”
Section: Discussionmentioning
confidence: 99%